PENERAPAN ALGORITMA K-MEANS PADA CLUSTERING VAKSINASI COVID-19 DAERAH JAWA TIMUR - MICHAEL SITORUS; CORNELIA ANTONIETA .DC.; CYNTIA LARASATI (JURNAL TEKNOSAINS KODEPENA, 2022)
Entering the era of the Covid-19 pandemic, the government has intensively implemented a vaccination program to date. The Covid-19 vaccination program is carried out as an effort to boost the immune system, reduce the risk of transmission, reduce the severe impact of the virus, to achieve group immunity. In its own implementation, the Covid-19 vaccination is regulated by the regional government in each province with a policy that requires the Covid-19 vaccination to be vaccinated twice for everyone who meets certain criteria. This study aims to cluster the implementation of vaccination in all areas of East Java province in 2021. The method used in conducting this clustering is the K-Means algorithm. From the results of the study, the results of the division or clustering of regions into three clusters were C1 for the area with the lowest vaccination, namely Pasuruan Regency, C2 for the area with moderate vaccination, namely Kediri City, and C3 for the highest vaccination area, namely Surabaya City. The clustering results obtained based on the K-Means algorithm can be used as input for the East Java Provincial government in evaluating the implementation of the Covid-19 vaccination.